2012
DOI: 10.12659/msm.882878
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological responses to progressive resistance exercise training in healthy young males

Abstract: SummaryBackgroundThis study aimed to explore the effects of progressive resistance exercise training (PRET) on hemorheology.Material/MethodsExercise sessions included 1–3 sets of 8–12 repetitions at 40–60% of 1-repetition maximum (1-RM) for 3 weeks and at 75–80% of 1-RM during weeks 4–12. Red blood cell (RBC) deformability and aggregation were determined by ektacytometry, plasma and whole blood viscosities (WBV) by rotational viscometry. Lactate concentration was evaluated by an analyzer and fibrinogen was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
(47 reference statements)
3
23
0
Order By: Relevance
“…Exercise training also induces adaptations of RBC aggregation [46] and RBC deformability [14]. Ernst et al [35] reported increased RBC deformability in athletes compared to sedentary subjects, a finding later confirmed by Smith et al [77].…”
Section: Healthy Populationmentioning
confidence: 88%
See 2 more Smart Citations
“…Exercise training also induces adaptations of RBC aggregation [46] and RBC deformability [14]. Ernst et al [35] reported increased RBC deformability in athletes compared to sedentary subjects, a finding later confirmed by Smith et al [77].…”
Section: Healthy Populationmentioning
confidence: 88%
“…Whereas acute exercise may increase blood viscosity at a given shear rate, chronic exercise (endurance or resistance exercise) usually results in a decrease [12,46,68]. Following a cessation of exercise (few hours or few days later), there is an increase in plasma volume [12] which represents a reversal of the acute hyperviscosity observed during acute exercise, resulting in an "autohemodilution" [35,36].…”
Section: Healthy Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, a change in RBC hemorheological parameters (RBC EI_3Pa: 3.31%, RBC AI_3Pa: −4.84%) was observed after 12 weeks of combined exercise training. Regular exercise (aerobic or resistance) usually reduces blood viscosity [53,54]. Exercise training also induces the rheological adaptation of RBCs [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma volume expansion during prolonged exercise might explain the decrease in hemoglobin while fall in RBC count could be attributed to either intravascular hemolysis from mechanical trauma [13], osmotic/oxidative damage to erythrocytes [14] or gastrointestinal bleeding [15]. This phenomenon -"sports anemia", is commonly encountered in endurance trained athletes due to the existence of a chronic dilutional state [16].…”
Section: Discussionmentioning
confidence: 99%